Fermented Extract of Senduduk Leaf as Herbal Additive to Reduce Escherichia coli Population in Broiler Cecum: Ekstrak Fermentasi Daun Senduduk Sebagai Aditif Herbal Untuk Menurunkan Populasi Escherichia coli Pada Sekum Broiler - Farhana, Nurul; Yulia, Eva; Fati, Nelzi; Ramaiyulis, Ramaiyulis (BPFP Universitas Bengkulu, 2024)
Escerichia coli is a type of bacteria that normally grows in the caecum of broilers and has the potential to become a pathogen that causes disease in broilers. This study aims to determine the effect of adding fermented sendunia leaf extract (EFDS) to drinking water on the population of Escherichia coli bacteria in the caecum of broilers. EFDS is obtained from the fermentation of fresh sendua leaves in a mixture of 1 kg of sendunia leaves + 1 l of EM4 + 16 l of sterile distilled water in a jerry can which is incubated for 2 weeks at room temperature. This study used a completely randomized design (CRD) with 4 treatments adding EFDS to drinking water at levels: A = 0% (control), B = 2%, C = 4%, and D = 6% with 5 replications. Lohman type broilers were kept for 5 weeks in cages measuring 60 x 100 cm containing 5 broilers for one treatment unit. The ration used contains 22% crude protein and 3000 Kcal/kg energy. The results of parameter measurements at the end of maintenance showed that the treatment with the addition of EFDS at levels of 4 and 6% showed that the diameter of the inhibition zone for Escherichia coli bacteria was classified as moderate level, namely 5.1-5.3 mm. A population decrease (P<0.05) was found at the EFDS level of 4% in drinking water with a population of 0.86 x106 CFU/ml with a decrease of 63.25% compared to the control. The addition of EFDS had no significant effect (P>0.05) on cecum pH and cecum length, but there was a tendency for pH to decrease (6.4-5.7) according to the level of EFDS addition. The addition of 4% EFDS in broiler drinking water is recommended in this study to control the Escherichia coli population in the broiler caecum.